Cost-effectiveness analysis of a randomized clinical trial of early versus deferred endovenous ablation of superficial venous reflux in patients with venous ulceration. Issue 5 (11th February 2019) - Epstein, D M; Gohel, M S; Heatley, F; Liu, X; Bradbury, A; Bulbulia, R; Cullum, N; Nyamekye, I; Poskitt, K R; Renton, S; Warwick, J; Davies, A H; et al.
Abstract: Background: Treatment of superficial venous reflux in addition to compression therapy accelerates venous leg ulcer healing and reduces ulcer recurrence. The aim of this study was to evaluate the costs and cost-effectiveness of early versus delayed endovenous treatment of patients with venous leg ulcers. Methods: This was a within-trial cost-utility analysis with a 1-year time horizon using data from the EVRA (Early Venous Reflux Ablation) trial. The study compared early versus deferred endovenous ablation for superficial venous truncal reflux in patients with a venous leg ulcer. The outcome measure was the cost per quality-adjusted life-year (QALY) over 1 year. Sensitivity analyses were conducted with alternative methods of handling missing data, alternative preference weights for health-related quality of life, and per protocol. Results: After early intervention, the mean(s.e.m.) cost was higher (difference in cost per patient £163(318) (€184(358))) and early intervention was associated with more QALYs at 1 year (mean(s.e.m.) difference 0·041(0·017)). The incremental cost-effectiveness ratio (ICER) was £3976 (€4482) per QALY. There was an 89 per cent probability that early venous intervention is cost-effective at a threshold of £20 000 (€22 546)/QALY. Sensitivity analyses produced similar results, confirming that early treatment of superficial reflux is highly likely to be cost-effective. Conclusion: Early treatment of superficial reflux is highly likely to be cost-effective in patients with venous leg ulcers over 1 year. Registration number: ISRCTN02335796 (http://www.isrctn.com ). Graphical Abstract: This study found that, in addition to compression therapy, early endovenous ablation of superficial reflux is highly likely to be cost-effective at UK decision-making thresholds. This reinforces the benefits of early intervention and should have a global impact on the management of patients with venous ulceration. Early intervention should be routine